SAT0129 Improved Quality of Life, Work Productivity, General Activity and Independence in Response to Subcutaneous Abatacept or Adalimumab in Rheumatoid Arthritis: Results from the Ample Trial. (23rd January 2014) - Fleischmann, R.; Weinblatt, M.; Schiff, M.; Khanna, D.; Rosenblatt, L.; Maldonado, M.; Furst, D.
Abstract : Background: Rheumatoid arthritis (RA) is associated with pain and impairment of physical function, significantly impacting a patient's health-related quality of life (HRQoL) and ability to perform daily activities. We report here comparative findings from patient reported outcomes (PROs) assessed with subcutaneous abatacept (ABA) or adalimumab (ADA) on background methotrexate (MTX) in the first head-to-head study, AMPLE (A batacept Versus Adalim umab Comp arison in Biol ogic Naive RA Subjects with Background Methotrexate). Objectives: To compare changes in PROs at 1 year in patients with RA treated with ABA or ADA, both on background MTX. Methods: AMPLE is a phase IIIb, randomized, investigator-blinded study of 2 year duration. Biologic-naïve patients with active RA and inadequate response to MTX were randomized to either 125 mg ABA weekly or 40 mg ADA bi-weekly in combination with MTX. PROs evaluated through Day 365 included: HRQoL assessed using SF-36 (including Physical and Mental Component Summary subscores [PCS and MCS]), activity limitation over the previous 30 days, with the Activity Limitation Questionnaire (ALQ) 1, productivity, with the work productivity and activity impairment questionnaire for RA(WPAI:RA) 2, physical and psychosocial independence, captured using items from HAQ, SF-36, and ALQ. 3 Other PROs previously reported from AMPLE, include: patient pain, patient global assessment, fatigue, and physical function. 4 All efficacy analyses were done using the intent-to-treat population. Baseline characteristics were analyzed descriptively and changes in PROs from baseline were assessed using ANCOVA. Results: Baseline demographic and clinical characteristics of the ABA (n=318) and ADA (n=328) treatment arms were similar 4 . Improvements in all domains of the SF-36, including PCS and MCS observed at Day 169 were maintained at Day 365. At baseline, the number of days (mean ± SD) with limited activity over the previous 30 days was 11.7 ± 10.4 and 12.4 ±10.3, respectively, for ABA and ADA. At Day 169, number of days with limited activity was reduced to 5.5 ± 8.2 and 5.9± 8.1, which remained sustained at Day 365 at 5.1 ± 7.4 and 6.1 ± 8.3 days for ABA and ADA, respectively. Improvements in productivity were seen in both treatment groups; however, numerically greater decreases in work and activity impairment were seen earlier at Day 169, with ABA; at Day 365, improvements were comparable among both treatment groups. At baseline, psychosocial independence was 0.3 ± 0.9 and 0.3 ± 0.8 for ABA and ADA respectively which improved at Day 365 to 1.0±1.0 and 1.0 ± 1.0. Physical independence improved from 0.5 ±1.1 and 0.5 ±1.0 at baseline to 1.4 ± 0.9 and 1.4±1.0 at Day 365 in the two groups. Conclusions: Both SC abatacept and adalimumab, on background MTX, led to comparable improvements in HRQoL, work productivity, activity limitation and physical and psychosocial independence. Improvements in these measures were evident at Day 169 and were sustained through Day 365. References: Wells G et al. J Rheumatol. 2007;34(2):280-289. http://www.reillyassociates.net/WPAI_SHP.html Hassett AL et al. Curr Med Res Opin. 2008;24(5):1443-1453. Weinblatt et al. Arthritis Rheum. 2013; 65 (1):28-38 Disclosure of Interest: R. Fleischmann Grant/research support from: Genentech Inc., Roche, Abbott, Amgen, UCB, Pfizer, Bristol-Myers Squibb, Eli-Lilly, Sanofi-Aventis, Lexicon, MSD, Novartis, BiogenIdec, Astellas, Astra-Zeneca, Jansen, Consultant for: (Roche, Abbott, Amgen, UCB, Pfizer, Bristol-Myers Squibb, Eli-Lilly, Sanofi-Aventis, Lexicon, Novartis, Astellas, Astra-Zeneca, Jansen, HGS, M. Weinblatt Grant/research support from: Bristol-Myers Squibb, Abbott, Consultant for: Bristol-Myers Squibb, Abbott, M. Schiff Consultant for: Bristol-Myers Squibb, Abbott, Speakers bureau: Bristol-Myers Squibb, Abbott, D. Khanna Consultant for: Bristol-Myers Squibb, L. Rosenblatt Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Maldonado Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, D. Furst Grant/research support from: Abbott, Actelion, Amgen, BMS, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: Abbott, Actelion, Amgen, BMS, BiogenIdec, Centocor, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers bureau: Abbott, Actelion, UCB (CME ONLY)